2009
DOI: 10.1007/s11626-009-9265-7
|View full text |Cite
|
Sign up to set email alerts
|

Newly established cell lines from mouse oral epithelium regenerate teeth when combined with dental mesenchyme

Abstract: The present study attempted to examine whether clonal cell lines of the oral epithelium can differentiate into ameloblasts and regenerate tooth when combined with dental germ mesenchyme. Clonal cell lines with a distinct morphology were established from the oral epithelium of p53-deficient fetal mice at embryonic day 18 (E18). The strain of mouse is shown to be a useful source for establishing clonal and immortalized cell lines from various tissues and at various stages of development. Tooth morphogenesis is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Therefore, there has been a concentrated effort in finding alternative sources of non-dental epithelial cells. One possible source may be the oral mucosa epithelium [101,102]. Transplantation of a mouse line of oral epithelial cells derived from p53-deficient embryos combined with embryonically derived dental mesenchymal cells under kidney capsule, exhibited some evidence of tooth formation [101].…”
Section: Therapeutic Applications Of Ncscs: Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there has been a concentrated effort in finding alternative sources of non-dental epithelial cells. One possible source may be the oral mucosa epithelium [101,102]. Transplantation of a mouse line of oral epithelial cells derived from p53-deficient embryos combined with embryonically derived dental mesenchymal cells under kidney capsule, exhibited some evidence of tooth formation [101].…”
Section: Therapeutic Applications Of Ncscs: Mscsmentioning
confidence: 99%
“…One possible source may be the oral mucosa epithelium [101,102]. Transplantation of a mouse line of oral epithelial cells derived from p53-deficient embryos combined with embryonically derived dental mesenchymal cells under kidney capsule, exhibited some evidence of tooth formation [101]. Although these results are encouraging, absence of a tumor suppressor gene is not ideal and ultimately isolation of epithelial cells with such capacities needs to become feasible in the adult.…”
Section: Therapeutic Applications Of Ncscs: Mscsmentioning
confidence: 99%
“…Another study reported the establishment of clonal cell lines when dental mesenchyme at embryonic day 16.5 were recombined with oral epithelium of p53 deficient fetal mice at embryonic day 18. Further these clonal cell lines formed calcified tooth structures as seen in natural teeth [31]. In a similar study by Komine A et al, clonal cell lines established from dental epithelium of a molar tooth germ were able to generate well calcified teeth [32].…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have suggested that palatal mucosal epithelium from post-natal mice can be grown as cell sheets in serum-supplemented medium in the presence of the ROCK inhibitor, Y-27632, and form tooth-like structures when combined with mouse-inducing mesenchyme (Nakagawa et al, 2009). In another study, with the oral epithelium of p53-deficient fetal mice at embryonic day 18 (E18), clonal cell lines were established that formed calcified structures as seen in natural teeth, when recombined with E16.5 dental mesenchyme (Takahashi et al, 2010). Another study provided evidence that the addition of exogenous FGF proteins was required for the formation of ameloblast-like cells in recombinations between human newborn skin keratinocyte progenitors and mouseinducing mesenchymal cells (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%